An annotated checklist of mites (Arachnida: Acari) of Zambia - Mwase, Enala T.; Baker, Anne S. (Zootaxa, 2006)
Published literature on the mites of Zambia (formerly Northern Rhodesia) is scanty and fragmentary. As a baseline for further work to enhance knowledge of this fauna, an annotated list of the taxa reported to date is presented. Data for 90 species or incompletely identified species (representing four orders, 42 families and 57 genera) are given. The mites originated from vertebrates, invertebrates, plants, bat guano, house dust and freshwater habitats. Seventeen species are either introduced predators that have evidently not established or are concluded to be incorrect records. A host/habitat–mite checklist is also provided.